1983
DOI: 10.3109/02844318309013111
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Fingertip Amputations with Bone Exposure: A Comparative Study between Surgical and Conservative Treatment Methods

Abstract: The long-term results following 36 surgically and 34 conservatively treated fingertip amputations with bone exposure are presented in a retrospective study. Surgery did not produce better results even though it was performed by skilled hand surgeons. The advantages of the conservative (mainly adhesive zinc tape) treatment method are pointed out. The regenerative capacity of the amputated fingertip is shown and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 12 publications
2
35
1
1
Order By: Relevance
“…In contrast, Soderberg et al [29] reported 11 cases of infection in a series of 36 fingertip amputations treated surgically. Chow and Ho [6] reported 17 % infection incidence in their retrospective comparison of surgically treated fingertips.…”
Section: Infectionmentioning
confidence: 98%
See 4 more Smart Citations
“…In contrast, Soderberg et al [29] reported 11 cases of infection in a series of 36 fingertip amputations treated surgically. Chow and Ho [6] reported 17 % infection incidence in their retrospective comparison of surgically treated fingertips.…”
Section: Infectionmentioning
confidence: 98%
“…The most commonly reported mean time to complete healing using conservative wound care alone was 4 weeks [6,23,27,29]. Small defects (<1 cm) with no bone involvement were frequently healed within 2 weeks [9,22,23,31].…”
Section: Time To Healingmentioning
confidence: 99%
See 3 more Smart Citations